Images of world creation as mythological foundation of conceptual thinking - Razauskas, Dainius (Religija ir kultūra, 2008)
The paper aims at the psychological connotations of mythological images of the world creation. One of the most popular ones, for instance, that is, the image of creation as consolidation, solidifying, fastening of some liquid, watery primal matter amounts to the conscious ordering of the psychical data thus making a solid “cosmos” out of the “chaos” of unconscious perception. Sometimes the world creation is imagined also as fencing it around, enclosing from the surrounding chaos (cf. the Northern mið-garðr, Old English middan-geard etc.), in other words, as de-termining or de-fining it, that is, making a de-finition of it. Again, the world creation can be imagined as seizing and squeezing it by hand (out of clay, in particular), and namely this image constitutes the idea of “concept” and “conception” (Latin con-ceptio < con-cipio, capio “seize”, similarly in many languages) and, therefore, grounds conceptual thinking as such. On the other hand, mysticism refers “to the use of concepts as filters to screen us from a direct perception of what is. The concepts are taken too seriously; they are used as tools to solidify our world and ourselves” (as expressed by Chögyam Trungpa, the representative of the Vajrayāna Buddhism). In its turn, the spiritual enlightenment and liberation are often representend figuratively by images akin to these of eschatology.
Keywords: mythology; cosmogony; creation; concept (conceptual thinking); eschatology